In Situ Observations of the Diurnal Variation in the Boundary Layer of Mature Hurricanes - Jun A. Zhang; Jason P. Dunion; David S. Nolan (Geophysical Research Letters)
Abstract Recent studies have suggested that the structure of tropical cyclones (TCs), especially the upper‐level clouds as indicated by satellite infrared brightness temperatures and precipitation, fluctuates with the diurnal cycle. The diurnal cycle of the low‐level structure, including the boundary layer, has not yet been investigated with observations. This study analyzes data from 2242 GPS dropsondes collected in mature hurricanes to investigate the diurnal variation of the mean boundary layer structure. A composite analysis is conducted to compare the kinematic and thermodynamic structure during nighttime (0–6 local time) vs in the afternoon (12–18 local time). The composites show that much stronger inflow occurs during nighttime and the moist entropy is also larger than that in the daytime. Grouping the dropsonde data into 6‐h time windows relative to the local time shows a clear diurnal signal of boundary layer inflow. The amplitude of the diurnal signal is largest at a radius of 250–500 km.